Vazio institucional e seu efeito nas capacidades dinâmicas - Camargo, Maria Adriana de Andrade (2018)
The studies in the field of dynamic capacities have considered some assumptions, such as environmental conditions, and ignored others, such as the institutional void. Thus, this thesis empirically develops and tests a model that investigates the effect of institutional void and environmental uncertainty on the dynamic capacities of firms. In order to analyze this process, it was adopted the modeling of structural equations as a set of data analysis techniques, using the PLS system (Partial Least Squares) system through a survey conducted with managers of companies from emerging (Brazil) and developed countries (USA). The research methodology used was a grounded and adapted survey of scales tested in the literature, aiming to measure the proposed constructs: dynamic capacities, environmental uncertainty and institutional void. A total of 261 valid responses (126 respondents from Brazil and 135 respondents from the United States) were received from managers and directors of Brazilian and US companies in the industry, agribusiness and services sectors. As a result, the study confirms that environmental uncertainty in both developed and emerging countries influences the dynamic capacities of firms and confirms that the institutional void has a positive effect on the development of the dynamic capacities of companies only in emerging countries. However, the institutional void does not appear as a driver of the development of dynamic capacities in developed country firms. The research corroborates the debates about dynamic capacity associated with environmental uncertainty, strengthens the discussion of the addition of the institutional void as another proposition of influence under the dynamic capacities of the companies and contributes presenting a model of references for future research that introduces the dynamic capacity of enterprises in the context of emerging and developed economies.